Eco-friendly composite hydrogel based on cellulose and bentonite for removal of lead (II): Kinetics and isotherm studies - Abiy Lolasa Obsa; Nurelegne Tefera Shibeshi; Eyobel Mulugeta; Getachew Adam Workeneh (Carbohydrate Polymer Technologies and Applications)
This study developed eco-friendly composite hydrogel based on cellulose and bentonite to remove Pb2+ from wastewater. The composite hydrogel adsorbents' morphology, chemical composition, and structure were characterized using FE-SEM, EDX, FT-IR, and XRD. Furthermore, EDX mapping displayed uniform dispersion of bentonite within the cellulose-based hydrogel (H), leading to enhanced swelling capacity and mechanical strength. To optimize the adsorption process, the effect of experimental conditions on the amount of Pb2+ adsorbed per bentonite/cellulose-based composite hydrogel (BCH3) was investigated. The batch adsorption results showed that the maximum adsorption capacity of Pb2+ onto BCH3 was 110.64 mg g-1. Post-adsorption EDX spectra and FTIR analysis provided evidence of successful Pb2+ uptake by BCH3. The results obtained from these analyses suggest that the primary adsorption mechanism involves the interaction of Pb2+ with nitrogen (NH2) and oxygen (COO-) groups on the BCH3 surface. Kinetics and isotherm data were best described by the pseudo-second-order (R2 = 0.999) and Sips models (R2 = 0.996). The kinetic model indicated that Pb2+ uptake onto the BCH3 was primarily governed by chemisorption involving coordination bonding/electrostatic interactions. The BCH3 adsorbent exhibited selectivity towards Pb2+ compared to Cd2+ and demonstrated good reusability after five adsorption-desorption cycles.